2014
DOI: 10.1155/2014/123079
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood WT1 Expression Predicts Relapse in AML Patients Undergoing Allogeneic Stem Cell Transplantation

Abstract: To evaluate if WT1 expression may predict relapse after allo-SCT, we analyzed WT1 levels on peripheral blood (PB) and bone marrow (BM) before and after allo-SCT in 24 AML patients with WT1 overexpression at diagnosis. Five copies of WT1/ABL × 104 from PB were identified as the threshold value that correlated with relapse after allo-SCT. The same correlation was not identified when WT1 expression was assessed from bone marrow (BM). Eight out of 11 (73%) patients with a pre-allo-SCT PB-WT1 ≥ 5 and 4/13 (31%) pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
3
17
0
Order By: Relevance
“…Therefore, a rising trend of WT1 expression indicates forthcoming clinical relapse. This is consistent with findings reported by Malagola et al [32]. We propose that patients who show changes in WT1 expression should be monitored more carefully and, if possible, treatment of the impending relapse should be started pre-emptively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, a rising trend of WT1 expression indicates forthcoming clinical relapse. This is consistent with findings reported by Malagola et al [32]. We propose that patients who show changes in WT1 expression should be monitored more carefully and, if possible, treatment of the impending relapse should be started pre-emptively.…”
Section: Discussionsupporting
confidence: 92%
“…Polák et al [20] noted that on the basis of BM-RNA the upper remission level was estimated to be the relative (WT1/ABL) expression of WT1 = 0.02. Malagola et al [32] chose five copies of WT1/ABL 9 10 4 from PB-RNA as the threshold value that correlated with relapse after allogeneic stem-cell transplantation [32]. In this study, we found that the WT1 expression level increased significantly, both in BM-RNA and CRNA, before clinical relapse.…”
Section: Discussionsupporting
confidence: 52%
“…Only taking into account the dynamic nature of this phenomenon, we can explain the discordance of the cut‐off values for positive versus negative samples observed by different groups. Also in our experience, for example, the predictive value of PB‐WT1 ≥ 16 × 10 4 ABL copies measured after 1st intensification is greater than PB‐WT1 ≥ 5 × 10 4 ABL copies measured before transplantation after completion of the treatment program, as already published on a selected cohort of the same patients .…”
Section: Discussionsupporting
confidence: 77%
“…Bone marrow and PB quantitative assessment of WT1 molecular levels was performed by Q‐PCR according to the ELN method as previously published .…”
Section: Methodsmentioning
confidence: 99%
“…In this strategy, Wilms tumor-1 (WT1) gene expression exceeding 100 copies/10 4 abelson murine leukemia-1 (ABL1) in bone marrow (BM) or WT-1 ≥5 copies/10 4 ABL1 in peripheral blood, with BM in remission status (<5% blasts simultaneously with morphology and cytometry symptoms) is surrogate for starting DLI [ 45 , 48 ]. In absence of GVHD for HLA identical siblings transplantation, the starting dosage is 1 × 10 6 /kg CD3+ cells and subsequently, half log increments every 30–60 days until MRD becomes negative.…”
Section: Pre-emptive/prophylactic Donor Lymphocyte Infusion In Hla Idmentioning
confidence: 99%